(untitled) (Medicine Today, 2025)
Introduction: The COVID-19 pandemic posed unprecedented challenges for the public health system worldwide, affecting low and middle-income countries like Bangladesh severely. In Dhaka, dense urban settlements, widespread miscommunication, and fear of the vaccine hindered the success of early vaccination. Traditional media did not reach the poor, so the Directorate General of Health Services (DGHS) had to make use of social media tools to promote the use of vaccines. Materials and Methods: This qualitative study spans Dhaka, Bangladesh, from January 2021 to December 2022. It analyses secondary data sources, including government reports, peer-reviewed journals, and social media. The digitally engaged urban youth, middle-class homes, and digitally excluded groups like slum dwellers and the elderly population are some of the targeted populations. Discussion: Social networking sites, primarily Facebook, YouTube, and Twitter, were instrumental in disseminating culturally appropriate, geolocated vaccine messages. The "Tika Dibo" campaign raised awareness and pushed registration via the ’Surokkha’ app, particularly among digitally literate youth. However, digital marginalization, limited monitoring of disinformation, and decentralized campaign management capped the overall effect. Strategic constraints included inadequate real-time feedback loops and no tailored communication for marginalized groups. Conclusion: Social media is a promising medium for low-cost and scalable public health outreach in urban LMIC settings. However, for optimal impact, online campaigns must be complemented by inclusive access strategies, timely monitoring of data, and better institutional coordination. Bangladesh’s experience offers important lessons for integrating social media into mainstream, long-term public health planning beyond emergency response contexts. Medicine Today 2025, Vol.37 (2): 167-170